Disparities Between Rural and Urban Patients With Prostate Cancer in Nebraska - Cassie Liu; Kaeli K. Samson; Oleg Shats; Raymond Bergan (Cancer Medicine)
ABSTRACT Introduction Studies focused on rural–urban disparities in patients with prostate cancer have demonstrated minimal differences in incidence and overall survival (OS). However, available data are limited, especially in understudied geographic locations. In this study, we investigated additional measures of potential cancer disparity and focused on examining rural–urban prostate cancer disparity in Nebraska residents. Methods Patients diagnosed with prostate cancer from 1991 to 2023 living in Nebraska were identified in the integrated Cancer Repository for Cancer Research (iCaRe2) and categorized as rural and urban by rural–urban commuting area (RUCA) codes. Results Results are presented as mean ± standard deviation. The iCaRe2 patient registry contained data on 765 men with prostate cancer living in Nebraska, 621 (81.2%) of whom were urban residents and 144 (18.8%) of whom were rural residents. Rural residents were diagnosed with prostate cancer 3.1 years younger than urban residents (rural: 65.6 ± 8.21 years, urban: 68.7 ± 9.08 years, p < 0.001). Rural residents died of prostate cancer 4.2 years younger than urban residents (rural: 72.9 ± 9.75 years, urban: 77.1 ± 8.85 years, p < 0.001). Analyses of Gleason score and AJCC stage did not reveal statistically significant differences between rural and urban residents. OS was similar between rural and urban men in Nebraska with prostate cancer, congruent with currently published literature. Conclusions Our analysis demonstrates that rural patients in Nebraska are diagnosed and die with prostate cancer at younger ages compared to urban patients. Our findings offer strategies to better define and delineate rural–urban cancer disparity and support future, more robust investigations to consider novel approaches to determining disparities in cancer disease course.